2007
DOI: 10.1080/02841860601137389
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous alteration ofde novoandsalvagepathway to the deoxynucleoside triphosphate pool by (E)-2′-Deoxy-(fluoromethylene)cytidine (FMdC) and zidovudine (AZT) results in increased radiosensitivityin vitro

Abstract: To test whether a thymidine analog zidovudine (=AZT), is able to modify the radiosensitizing effects of (E)-2'-Deoxy-(fluoromethylene)cytidine (FMdC). A human colon cancer cell line Widr was exposed for 48 hours prior to irradiation to FMdC. Zidovudine was added at various concentrations immediately before irradiation. We measured cell survival and the effect of FMdC, AZT and FMdC + AZT on deoxynucleotide triphosphate pool. FMdC results in a significant increase of radiosensitivity. The enhancement ratios (ER … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
(19 reference statements)
0
11
0
Order By: Relevance
“…As a result, the dNTP synthesis pathway is the predominant mechanism for supplying dNTPs in the brain. 71,72 The DNA repair pathway for removal of an incorrect DNA base, such as one of the most abundant alcohol-induced DNA base lesions oxo8dG, is BER. 73 Acetaldehyde-derived cross-links are repaired by the FA-linked pathway, coordinated with classical NER, applicable to non-replicating cells such as neurons.…”
Section: Alcohol and Ocmmentioning
confidence: 99%
“…As a result, the dNTP synthesis pathway is the predominant mechanism for supplying dNTPs in the brain. 71,72 The DNA repair pathway for removal of an incorrect DNA base, such as one of the most abundant alcohol-induced DNA base lesions oxo8dG, is BER. 73 Acetaldehyde-derived cross-links are repaired by the FA-linked pathway, coordinated with classical NER, applicable to non-replicating cells such as neurons.…”
Section: Alcohol and Ocmmentioning
confidence: 99%
“…Also, in irradiated human colon cancer cells,4 in irradiated human larynx squamous carcinoma cells,5 and in irradiated human malignant glioma cells6, 3′-AZT has been shown to be a significant radiosensitizer. Furthermore, it has been reported that 3′-AZT substantially enhances γ-irradiation killing of EBV (Epstein-Barr virus)-transformed lymphoblastoid cells in vitro 7…”
Section: Introductionmentioning
confidence: 99%
“…A direct correlation between cell death and micronuclei-induction was obtained in HeLa cells exposed at increasing doses of γ-irradiation in the presence of an aqueous solution (0.1 µM) of 3′-AZT [129]. Moreover, 3′-AZT causes significant radiosensitization in irradiated human colon cancer cells [130], in irradiated human larynx squamous carcinoma cells [131], and in irradiated human malignant glioma cells [132]. 3′-AZT substantially enhanced γ-irradiation killing of EBV (Epstein-Barr virus)-transformed lymphoblastoid cells in vitro [133].…”
Section: C5-modified Pyrimidine Nucleosides As Radiosensitizers (Rmentioning
confidence: 99%